The Role of Islam in the Development of the Arabic Language: History and Influence - Mohammad Iqbal Gusti Rakasiwi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Arabic language was formed long before the arrival of Islam, also known as the al-Asru al-jahili period. Arabic is part of the South Semitic language family spoken by the people living in the Arabian Peninsula, southwest of the Asian continent, and is considered by some to be the oldest historical language. As it developed, Arabic is now the official language of various countries, including Qatar, Chad, Palestine, Morocco, Egypt, Lebanon, Libya, Sudan, Oman, Gambia, Somalia, Iraq, Tunisia, and many more. There is still much debate about the history of the Arabic language, due to the lack of concrete evidence in the form of artifacts and other evidence proving its origin. This makes it difficult to prove its origin and when. The big question is whether Arabic is a descendant of a Semitic language or is it actually its parent language. Linguists have two opinions: one is that Arabic is a descendant of a Semitic language, based on the many similarities and similarities in the linguistic elements. Another view holds that Arabic is the mother of all other languages, and even the source of all other languages. Historians agree that the earliest evidence and documentation of Arabic texts was found in the 3rd to 5th centuries AD, known as al-Asru al-Jahili.